Analysis of Factors Affecting Patient Satisfaction of Social Health Insurance Administration Body Participants Non-Beneficiaries of Contribution Assistance at Kasih Ibu Lhokseumawe Hospital - Sri Lestari Ramadhani Nasution; T Saiful Muammar; Erni Girsang; Tan Suyono (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Patient satisfaction is an important and main thing that must be of concern to health facilities in providing their services. Factors that affect inpatient satisfaction are as follows: doctor services, nursing services, medical support services, administrative services, inpatient room facilities. This study aims to analyze the factors that influence patient satisfaction of Non-Recipient Social Security Agency participants at Kasih Ibu Lhokseumawe Hospital in 2022. This research is a quantitative study using descriptive analysis with a cross sectional design. The number of samples in this study were 207 inpatients. Data analysis that will be carried out is univariate, bivariate, multivariate analysis. Bivariate data analysis is intended to analyze the relationship between the independent variable and the dependent variable using the chi-square statistical test with a p value <0.05 declared significant. Multivariate analysis uses multiple logistic regression test analysis with modeling at the level of significance p < 0.05 and CI (Confidence Interval) and variables that become candidate models have a p value < 0.25. Furthermore, to determine significant variables using a 95% confidence interval (α = 0.05). Software in analyzing using SPSS statistics version 20. Based on the data from the research and after analysis and discussion, the author can conclude the findings of this study that Doctor services, nursing services, drug availability, inpatient room facilities, and the competence of health workers affect the satisfaction of patients participating in social health insurance administration body non-beneficiaries of contribution assistance at Kasih Ibu Lhokseumawe General Hospital. And Medical Support Services, Administration Services and Timely Services does not affect patient satisfaction of social health insurance administration body participants who are non-beneficiaries of contribution assistance at Kasih Ibu Lhokseumawe General Hospital. Keywords : External Factors, Internal Factors, Patient Satisfication, Participants